2023
DOI: 10.3390/ijms24043483
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Homeostasis in VSMCs as a Central Hub in Vascular Remodeling

Abstract: Vascular remodeling is a common pathological hallmark of many cardiovascular diseases. Vascular smooth muscle cells (VSMCs) are the predominant cell type lining the tunica media and play a crucial role in maintaining aortic morphology, integrity, contraction and elasticity. Their abnormal proliferation, migration, apoptosis and other activities are tightly associated with a spectrum of structural and functional alterations in blood vessels. Emerging evidence suggests that mitochondria, the energy center of VSM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 95 publications
0
11
0
Order By: Relevance
“…As an important part of the mitochondrial quality control system, the normal operation and coordination of mitochondrial ssion and mitophagy can protect the integrity of the inner and outer membrane structure of mitochondria, thereby maintaining the integrity of mtDNA and mitochondrial membrane potential (16,22). Once the mitochondrial structure is damaged and the damaged mitochondria cannot clear themselves in time, the damaged mitochondria will produce an ROS storm, destroy the redox balance, and then lead to cell death (33). However, it is still unclear as to how PARP1/POLG regulates UCP2.…”
Section: Discussionmentioning
confidence: 99%
“…As an important part of the mitochondrial quality control system, the normal operation and coordination of mitochondrial ssion and mitophagy can protect the integrity of the inner and outer membrane structure of mitochondria, thereby maintaining the integrity of mtDNA and mitochondrial membrane potential (16,22). Once the mitochondrial structure is damaged and the damaged mitochondria cannot clear themselves in time, the damaged mitochondria will produce an ROS storm, destroy the redox balance, and then lead to cell death (33). However, it is still unclear as to how PARP1/POLG regulates UCP2.…”
Section: Discussionmentioning
confidence: 99%
“…65 Further, in CVD, diseased VSMC exhibit reduced mitochondrial DNA content and a decrease in oxygen consumption rate (OCR), limiting their contractile ability. 66,67 Dysregulation of Ca 2+ channel function by ROS similarly affects respiration in VSMC as cardiomyocytes by impeding Ca 2+ transport. 68 Ca 2+ dysregulation in VSMC can additionally promote an osteochondrogenic phenotype and the increase of vascular calcification, which is correlated with acute cardiovascular event propensity.…”
Section: Vascular Smooth Muscle Cellsmentioning
confidence: 99%
“…Preliminary studies have shown that targeting VSMC senescence by increasing transcription of Kruppel‐like factor (KLF5) can reduce mitochondrial fission 65 . Further, in CVD, diseased VSMC exhibit reduced mitochondrial DNA content and a decrease in oxygen consumption rate (OCR), limiting their contractile ability 66,67 . Dysregulation of Ca 2+ channel function by ROS similarly affects respiration in VSMC as cardiomyocytes by impeding Ca 2+ transport 68 .…”
Section: Introduction To Mitochondrial Function and Dysfunctionmentioning
confidence: 99%
“…However, no studies on the relationship between S100A6 and VSMCs have been published. The changes in VSMC structure and function are closely related to the occurrence of cardiovascular diseases (Grootaert and Bennett 2021 ; Xia et al 2023 ). During the development of atherosclerosis, abnormal proliferation and migration of VSMCs and the synthesis of the extracellular matrix by these cells are important contributors to early vascular injury (Vacante et al 2021 ).…”
Section: S100 Proteins In Cardiovascular Diseasesmentioning
confidence: 99%